1999
DOI: 10.1038/20646
|View full text |Cite
|
Sign up to set email alerts
|

Weak surface anchoring of liquid crystals

Abstract: letters to nature 338 NATURE | VOL 399 | 27 MAY 1999 | www.nature.comWith Ṁ 2 suppressed, the performance of the engine is measured as a function of p 1c and the temperature of the helium immediately below the hot heat exchanger, T h,gas . Figure 3 shows the thermal efficiency 2 , h ¼Ẇ res =Q h , where Ẇ res is the acoustic power delivered to the resonator. The maximum thermal efficiency of h ¼ 0:30 occurs near jp 1 =p m j ¼ 0:06 at T h;gas ¼ 725 ЊC with the engine delivering 710 W to the resonator. This corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
85
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(86 citation statements)
references
References 10 publications
1
85
0
Order By: Relevance
“…A simple model used to simulate the transition not only showed good agreement with the experiment but also revealed that the polar surface energies of the frustrated boundary are only 1=10 of typical values. Weak surface anchoring energies are virtuous for lowering device energy consumption and response time [9]. Figure 1 shows a subset of the microtextured substrates employed in this study.…”
mentioning
confidence: 99%
“…A simple model used to simulate the transition not only showed good agreement with the experiment but also revealed that the polar surface energies of the frustrated boundary are only 1=10 of typical values. Weak surface anchoring energies are virtuous for lowering device energy consumption and response time [9]. Figure 1 shows a subset of the microtextured substrates employed in this study.…”
mentioning
confidence: 99%
“…In fact, the threshold voltage indirectly depends on the RM doping concentration in terms of the polar anchoring energy, in such way that it decreases with decreasing anchoring energy. Moreover, as shown in Figure 4(a), the slope of the EO curve of the LC cell with a 2.5 wt% RM concentration was quite steep, indicating the weak-anchoring case [24]. Now, the polar anchoring energy is determined using a high-electric-field method [25][26][27][28].…”
Section: Resultsmentioning
confidence: 99%
“…The threshold intensity is determined by three balancing factors that interact with an optical field of polarized light: molecular polarizability, bulk elasticity and surface anchoring. Considering previous reports, 16,30,31 it is assumed that the threshold intensity for photoinduced molecular reorientation can be reduced by weakening the surface anchoring. This assumption was confirmed by direct evaluation of optical nonlinearity in self-diffraction ring measurements.…”
Section: Evaluation Of Optical Nonlinearity Of Pslcsmentioning
confidence: 99%
“…[30][31][32][33][34] Seki et al 33 and Aoki et al 34 revealed that the packing density of azobenzene units over the substrate surface influences the molecular reorientation behavior of LCs. Here we report that surface treatment drastically affects and reduces the threshold intensity for molecular reorientation in dye-doped LCs.…”
Section: Introductionmentioning
confidence: 99%